2023
DOI: 10.3389/fnut.2023.1151801
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient recovery in cultured meat systems: Impacts on cost and sustainability metrics

Abstract: A growing global meat demand requires a decrease in the environmental impacts of meat production. Cultured meat (CM) can potentially address multiple challenges facing animal agriculture, including those related to animal welfare and environmental impacts, but existing cost analyses suggest it is hard for CM to match the relatively low costs of conventionally produced meat. This study analyzes literature reports to contextualize CM’s protein and calorie use efficiencies, comparing CM to animal meat products’ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Beef is a good source of protein and essential nutrients such as Fe and Zn, which are important for maintaining a healthy immune system ( 19 ) . The causal relationship observed between beef intake and COVID-19 hospitalisation risk may be due to a number of factors, including the nutritional content of beef and its potential effects on the immune system or underlying health conditions ( 20 ) . For example, previous studies have suggested that certain nutrients in beef, such as Zn and vitamin B 12 , may have a beneficial effect on the immune system, potentially reducing the risk of viral infections ( 21 , 22 , 23 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Beef is a good source of protein and essential nutrients such as Fe and Zn, which are important for maintaining a healthy immune system ( 19 ) . The causal relationship observed between beef intake and COVID-19 hospitalisation risk may be due to a number of factors, including the nutritional content of beef and its potential effects on the immune system or underlying health conditions ( 20 ) . For example, previous studies have suggested that certain nutrients in beef, such as Zn and vitamin B 12 , may have a beneficial effect on the immune system, potentially reducing the risk of viral infections ( 21 , 22 , 23 ) .…”
Section: Discussionmentioning
confidence: 99%